Prediction of metabolic syndrome by visceral adiposity index, lipid accumulation product and model of adiposity index amongst infertile women with and without polycystic ovary syndrome - Saxena, Pikee; Gaur, Jyoti; Mishra, Archana; Jain, Anju (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: This study was conducted to compare visceral adiposity index (VAI), lipid accumulation product (LAP) and model of adiposity index (MAOD) for prediction of metabolic syndrome (MS) amongst infertile women with and without PCOS. Methods: It was a case control, retrospective study performed in gynecology outpatient department of a tertiary care center. Total 143 infertile women with PCOS and 367 infertile women without PCOS were recruited in the study. Waist circumference (WC), BMI, waist hip ratio (WHR), insulin resistance, VAI, LAP, MOAD were assessed in both groups. Results: Significantly higher values of WC, WHR, systolic BP, insulin postprandial and all 3 adiposity indices were found among infertile women with PCOS as compared to women without PCOS. In hormonal profile, testosterone, AMH, FSH, prolactin, estradiol was found to be significantly higher in PCOS group. For predicting MS in PCOS women, VAI had the highest AUC 0.878 with a cut off value of 3.1, highest sensitivity of 88.9%, specificity of 90.7%, positive and negative predictive value of 76.2% and 96% respectively followed by LAP and MOAD. Conclusions: To conclude, all three adiposity indexes VAI, LAP and MOAD were significantly raised in PCOS women. VAI followed by LAP were the best indicators to predict metabolic syndrome in women with PCOS.